Pengaruh Metode Pembelajaran dan Keterlibatan Siswa dalam Program BSI Explore Terhadap Minat Belajar di SDN Kampung Melayu V - Arjuna Dimas Saputra; Saddam Hussaen; Septi Setyaningsih; Fathia Maulina; Sherli Gita Indah Sari; Gusti Setiawan (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2025)
This study aims to analyze the influence of interactive teaching methods and student involvement on student learning interest and motivation at SDN Kampung Melayu V through the BSI Explore Program. Using a quantitative descriptive approach with a survey, data were collected through questionnaires filled out by students participating in the program. The results show a significant positive impact between interactive teaching methods and active student involvement on the improvement of their learning interest and motivation. Students who actively participated in activities such as discussions, experiments, and practical tasks showed higher levels of learning interest compared to those who were less involved. These findings underline the importance of using teaching methods that prioritize active interaction to improve the quality of education and student motivation. Therefore, the results of this study recommend integrating interactive teaching methods and active student involvement into educational programs to encourage greater learning interest among students.